If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7x + -8y + -3x + 12y = 0 Reorder the terms: -7x + -3x + -8y + 12y = 0 Combine like terms: -7x + -3x = -10x -10x + -8y + 12y = 0 Combine like terms: -8y + 12y = 4y -10x + 4y = 0 Solving -10x + 4y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4y' to each side of the equation. -10x + 4y + -4y = 0 + -4y Combine like terms: 4y + -4y = 0 -10x + 0 = 0 + -4y -10x = 0 + -4y Remove the zero: -10x = -4y Divide each side by '-10'. x = 0.4y Simplifying x = 0.4y
| 9(a+7)=96.3 | | x^5-6x^2+9x=0 | | -821-144-48-(-830)= | | x^2-20x+11=-7x-1 | | 1.8=3c-3 | | 14x+(-10y)+(-3)+6y= | | x^2+12x+35=3 | | 2+(x+17)= | | 7+(-2)+(-2)+7= | | x^2-3y^2=1 | | 4x^2-15x+11=-8x+8 | | 49x^2-84+36=0 | | 7(5a+b)+4(3a+4b)= | | 6e-6=15.6 | | (7x+3)9= | | 8x-6(x+8)= | | 83-6x=30x+23 | | 3x+9(x+7)= | | 8d+9=5d+30 | | =(x^2+y^2+1)(x^2+y^2+1) | | 2x^2+2y^2+2xy-10x-8y+14=0 | | =(4x-3y-1)(4x-3y-1) | | 2x^2-35x+2=0 | | =(3x^2-5y)(3x^2-5y)(3x^2-5y) | | =(2x^3y+z^2)(2x^3y+z^2)(2x^3y+z^2) | | 5x+3=(x-21) | | =(m^2n+8)(m^2n+8)(m^2n+8) | | =(m^2+8)(m^2+8)(m^2+8) | | =(5x-y)(2x-3) | | =(x+8y)(x-6y) | | 2(15-5)-(7-8)= | | 2(-31)= |